Large Cervical Vagus Nerve Tumor in a Patient with Neurofibromatosis Type 1 Treated with Gross Total Resection: Case Report and Review of the Literature - Bray, David P.; Chan, Andrew K.; Chin, Cynthia T.; Jacques, Line (Journal of Brachial Plexus and Peripheral Nerve Injury, 2016)
Neurofibromas are benign peripheral nerve sheath tumors that occur commonly in individuals with neurocutaneous disorders such as neurofibromatosis type 1. Vagal nerve neurofibromas, however, are a relatively rare occurrence. We present the case of a 22-year-old man with neurofibromatosis type 1 with a neurofibroma of the left cervical vagal nerve. The mass was resected through an anterior approach without major event. In the postoperative course, the patient developed left vocal cord paralysis treated with medialization with injectable gel. We then present a comprehensive review of the literature for surgical resection of vagal nerve neurofibromas.
Keywords: vagus nerve tumor; cervical vagus nerve; neurofibromatosis type 1; neurofibroma; neck mass; diffusion tensor imaging